Free Universal Construction Kit: On appropriation and parasites - Hansen, Lone Koefoed; Stephensen, Jan Løhmann (AoIR Selected Papers of Internet Research, 2013)
With the increasing economic accessibility of 3D printers, the lessons learned and the logics cultivated on digital Web 2.0 now seems applicable to the world of material things. Released in early 2012 by the artist groups F.A.T. and Sy-lab, the Free Universal Construction Kit is a set of 3D drawings that, when printed, enable everyone with access to a 3D printer to make connectors, “the missing links”, between intellectual property restricted toy concepts like LEGO, Tinkertoys, and Fischertechnik. However, when describing this project as “reverse engineering as a civic activity”, it seems obvious that F.A.T.’s greater agenda is not just to enable cross-over playing but rather to problematize and ultimately open up closed formats through critical appropriation. But how does that, for instance, conform with the fact that the connectors are parasitically attached to these toys, whose logic it is simultaneously defying?